Epac1 Blocks NLRP3 Inflammasome to Reduce IL-1β in Retinal Endothelial Cells and Mouse Retinal Vasculature. (28th February 2017) - Jiang, Youde; Liu, Li; Curtiss, Elizabeth; Steinle, Jena J.
Abstract : Inflammation is an important component of diabetic retinal damage. We previously reported that a novel β -adrenergic receptor agonist, Compound 49b, reduced Toll-like receptor 4 (TLR4) signaling in retinal endothelial cells (REC) grown in high glucose. Others reported that TLR4 activates high-mobility group box 1 (HMGB1), which has been associated with the NOD-like receptor 3 (NLRP3) inflammasome. Thus, we hypothesized that Epac1, a downstream mediator of β -adrenergic receptors, would block TLR4/HMGB1-mediated stimulation of the NLRP3 inflammasome, leading to reduced cleavage of caspase-1 and interleukin-1 beta (IL-1 β ). We generated vascular specific conditional knockout mice for Epac1 and used REC grown in normal and high glucose treated with an Epac1 agonist and/or NLRP3 siRNA. Protein analyses were done for Epac1, TLR4, HMGB1, NLRP3, cleaved caspase-1, and IL-1 β . Loss of Epac1 in the mouse retinal vasculature significantly increased all of the inflammatory proteins. Epac1 effectively reduced high glucose-induced increases in TLR4, HMGB1, cleaved caspase-1, and IL-1 β in REC. Taken together, the data suggest that Epac1 reduces formation of the NLRP3 inflammasome to reduce inflammatory responses in the retinal vasculature.